Tuberous sclerosis: possible modification of phenotypic expression by an unlinked dominant gene. - Rushton, A R (1979)
A unique pedigree is presented which shows tuberous sclerosis in three generations of a family, in which two heterozygotes for the mutant gene were found to be clinically asymptomatic. A genetic model is proposed to explain these findings based upon the segregation of a second unlinked autosomal dominant gene modifying the expression of the gene for tuberous sclerosis.